2020
DOI: 10.1007/s11684-020-0767-8
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 (COVID-19): a clinical update

Abstract: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has posed a significant threat to global health. It caused a total of 80 868 confirmed cases and 3101 deaths in Chinese mainland until March 8, 2020. This novel virus spread mainly through respiratory droplets and close contact. As disease progressed, a series of complications tend to develop, especially in critically ill patients. Pathological findings showed representative features of acute respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
414
1
45

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 417 publications
(463 citation statements)
references
References 60 publications
(83 reference statements)
3
414
1
45
Order By: Relevance
“…Parts of the lung can have alveolar exudate organization and pulmonary interstitial fibrosis. 7 The presence of microthrombi fits with the observation that abnormal coagulation parameters, including increased plasma d-dimers, are associated with poor prognosis. 8 Anecdotal evidence suggests that peripheral pulmonary thrombosis or embolism might be common in patients with severe COVID-19 (https://renal.org/wp-content/uploads/ 2020/04/COVID-19_synthesis-of-clinical-experience-in-UK-intensive-care_04.04.2020_FINAL.pdf).…”
Section: Introductionsupporting
confidence: 73%
“…Parts of the lung can have alveolar exudate organization and pulmonary interstitial fibrosis. 7 The presence of microthrombi fits with the observation that abnormal coagulation parameters, including increased plasma d-dimers, are associated with poor prognosis. 8 Anecdotal evidence suggests that peripheral pulmonary thrombosis or embolism might be common in patients with severe COVID-19 (https://renal.org/wp-content/uploads/ 2020/04/COVID-19_synthesis-of-clinical-experience-in-UK-intensive-care_04.04.2020_FINAL.pdf).…”
Section: Introductionsupporting
confidence: 73%
“…Excessive immune responses can trigger cytokine storms and cause damage to multiple target organs. Recent guidelines also point that a progressive rise in IL-6 may be a clinical warning indicator for the deterioration of COVID-19 13 . Tocilizumab, a monoclonal antibody against interleukin-6, emerged as an alternative treatment for COVID-19 patients with a risk of cytokine storms recently 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from infections in special contexts such as cruise liners (9) and in close contacts of COVID-19 patients (10) have demonstrated that SARS-CoV-2-specific RT-PCR may be positive in the early phase of the disease, and that viral shedding in the asymptomatic phase and in the early prodromal phase can be considerable. (11,12) At present screening of asymptomatic individuals by RT-PCR has been constrained by limited testing capacity, and the need to focus on public health efforts and resources on symptomatic persons.…”
Section: Clinical and Immunodiagnostic Trajectory Of Covid-19 And Sammentioning
confidence: 99%